Juvenile Papillomatosis: A Case Report - Valerie Vandeweerd; Machteld Keupers; Griet Hoste; Tom Langenaeken; Patrick Neven (European Journal of Breast Health, 2019)

(untitled)
Juvenile papillomatosis of the breast, also known as Swiss cheese disease, is a rare and benign proliferative disorder affecting young women. These patients tend to have a strong family history of cancer. The lesion typically presents as a localized mass without sharp borders. Clinical presentation resembles that of a precancerous lesion. For this reason, JP is often misdiagnosed in the preoperative period. However postoperative histopathological examination reveals distinct microscopic features, such as duct papillomatosis, cysts and sclerosing adenosis, which confirm the diagnosis of juvenile papillomatosis. We report two cases of juvenile papillomatosis. Both cases were preoperatively diagnosed as benign proliferative lesions with fibrocystic changes. However, after surgical excision, histopathological examination showed juvenile papillomatosis. Interestingly, both patients had a strong family history of breast cancer in both the paternal and maternal line. More research is needed to assess the correlation between a family history of breast cancer and the juvenile papillomatosis.